A Content Analysis Of English For Nusantara Grade Ix Textbook Based On Elt Principles - Ellin Nurhayati; Rachel Putri Andra; Fransisca Indah Sulistyowati; Rizka Radiana; Elyza Martiarini (International journal of technology and education research, 2026)
This study aims to analyze the alignment of the pedagogical aspects of the English for Nusantara textbook with the principles of the Independent Curriculum. The evaluation was conducted to identify the extent to which the textbook supports student-centered learning, the development of communicative competence, the integration of language skills, the strengthening of critical thinking, and the implementation of the Graduate Profile values. This study employed a qualitative content analysis method, using the English for Nusantara textbook as the primary data source. Data were analyzed through a process of identification, classification, interpretation, and evaluation of the learning objectives, learning activities, language skills integration, assessment, and character development contained in the textbook. The results indicate that English for Nusantara has generally implemented the pedagogical principles of the Kurikulum Merdeka well. This textbook has clear learning objectives, implements a student-centered learning approach, integrates listening, speaking, reading, and writing skills in a balanced manner, and encourages the development of critical thinking skills through communicative, collaborative, and contextual activities. This research also identified several weaknesses, including limited differentiated learning activities to accommodate differences in student abilities, the reliance of some activities on teacher guidance, and the need for technological support for audio- and visual-based activities. The development of the textbook in the next edition needs to strengthen differentiated learning strategies, expand the variety of assessment forms, and provide activities that are more adaptive to the diversity of student abilities and learning conditions to ensure optimal implementation of the Independent Curriculum.